2007
DOI: 10.1103/physrevb.76.035410
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between electronic and atomic structures in the Si(557)-Au reconstruction from first principles

Abstract: The quasi-one-dimensional Si͑557͒-Au reconstruction has attracted a lot of attention in recent years. We study here the interplay between the electronic and structural degrees of freedom in this system. Our calculations are in good agreement with recent experimental data obtained using scanning tunneling microscopy and spectroscopy both at room and low temperatures. Together with the quite successful description of the experimental band structure, these results give further support to the current structural mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 56 publications
(113 reference statements)
9
58
2
Order By: Relevance
“…In previous investigations, we found that this was crucial to reduce the number of dangling bonds in the final structures and to facilitate the appearance of the so-called honeycomb-chain structure. 9 The honeycomb chain was proposed by us 7,9,11,16,18 and by other authors 3,5 as one of the key ingredients of the reconstructions induced by gold on Si͑111͒ vicinal surfaces, and the results presented here seem to confirm this idea. We have developed a compact notation that allows us to label and identify all of the structures.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In previous investigations, we found that this was crucial to reduce the number of dangling bonds in the final structures and to facilitate the appearance of the so-called honeycomb-chain structure. 9 The honeycomb chain was proposed by us 7,9,11,16,18 and by other authors 3,5 as one of the key ingredients of the reconstructions induced by gold on Si͑111͒ vicinal surfaces, and the results presented here seem to confirm this idea. We have developed a compact notation that allows us to label and identify all of the structures.…”
Section: Discussionsupporting
confidence: 79%
“…13,38 These bands are half filled and exhibit, as the temperature is lowered, a metal-insulator transition that is accompanied by a periodicity doubling along the steps in the STM images. [12][13][14]16 The Si͑553͒-Au surface, which has a smaller terrace width, shows two bands similar to those observed in the case of the Si͑557͒-Au system. It also shows a strongly dispersing one-dimensional band with a fractional ͑ϳ1 / 3͒ filling.…”
Section: Introductionsupporting
confidence: 48%
See 3 more Smart Citations